PENGARUH ZAKAT DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA BANK UMUM SYARIAH DAN UNIT USAHA SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rafika Uksi; A. Musyarrafah Vetriyani; Nurul Jannah Tahang (CV SWA Anugrah, 2024)
The aims of this research are : ( 1 ) analyze the effect of zakat on performance; ( 2 ) analyze the effect of social responsibility towards performance. This research used secondary data in the form of annual report and financial report commercial banks syariah and syariah business unit listed on the Indonesian Stock Exchange period 2015-2017 that can be accessed in each the banking official websites. With the total of samples from 11 banks with 33 observations.Data analyzed using SPSS program (Statistical Package For Social Science) version24.0.This research result indicates that: ( 1 ) zakat had a positive impact significantly to performance;( 2 ) social responsibility had a negative impact not significant to performance.